Palliative care case conferences in long‐term care: views of family members. (17th December 2015) - Parker, Deborah; Clifton, Karen; Tuckett, Anthony; Walker, Helen; Reymond, Elizabeth; Prior, Teresa; McAnelly, Kristien; Jenkin, Peter; Israel, Fiona; Greeve, Kim; Glaetzer, Karen
Abstract : Aims and objectives: This paper examines the use of structured Palliative Care Case Conferences in long‐term care. The issues families bring to the Palliative Care Case Conference, their level of distress prior to the conference, the extent to which these issues are addressed by staff and family satisfaction with this process are described. Background: In most developed countries, up to 30% of older people die in long‐term care. A palliative approach generally refers to the resident and family as the 'unit of care'. Interventions, which include family in palliative care, are required in this setting. Design: Descriptive and thematic results from the intervention arm of a pre–post, sequential mixed method study. Methods: Examination of documents of 32 resident/family dyads participating in a Palliative Care Case Conference, and interviews with the residents' family postintervention. Results: Main concerns raised by family members prior to a Palliative Care Case Conference were physical and medical needs, pain, end‐of‐life care planning and nutrition and hydration. Families rated a high level of concern, 7.5 on a 10‐point rating scale, prior to the Palliative Care Case Conference. A formalised Palliative Care Case Conference process ensured issues relating to end‐of‐life care planning, pastoral care, pain and comfort and physical and medical needs were well documented by staff. Issues relating to care processes and the family role in care were less well documented. All families, interviewed postintervention, recommended Palliative Care Case Conferences; and over 90% of families felt their issues were addressed to their satisfaction. Families also reported an increased understanding of the resident's current and future care. Conclusions: The Palliative Care Case Conference in long‐term care provides an important platform for family to voice concerns. Palliative Care Case Conference documentation indicates that staff are attending to these issues, although more reference to concerns relating to care processes and the family role could be made. Implications for practice: Increased communication between staff and family, in the form of a Palliative Care Case Conference, may reduce stress, anxiety and unwanted hospitalisations during the palliative phase.